2017
DOI: 10.1017/mor.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Ties, Market Orientation, and Export Performance: Chinese Firms Experience

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 133 publications
(346 reference statements)
0
11
1
2
Order By: Relevance
“…This paper contributes to institutional theory by investigating the institutional pressures that are related to the KM processes. Even though the literature indicates the prevalence of the Chinese government's influences and stresses the importance of political ties in business (Ma and Lu, 2017;Yan et al, 2017), coercive pressure did not affect the KM processes of organizations in our study. This finding suggests that coercive pressure might be contextspecific, such as forging and maintaining cordial relations, rather than how organizations manage knowledge in general.…”
Section: Research and Practical Implicationscontrasting
confidence: 70%
See 1 more Smart Citation
“…This paper contributes to institutional theory by investigating the institutional pressures that are related to the KM processes. Even though the literature indicates the prevalence of the Chinese government's influences and stresses the importance of political ties in business (Ma and Lu, 2017;Yan et al, 2017), coercive pressure did not affect the KM processes of organizations in our study. This finding suggests that coercive pressure might be contextspecific, such as forging and maintaining cordial relations, rather than how organizations manage knowledge in general.…”
Section: Research and Practical Implicationscontrasting
confidence: 70%
“…An early study conducted by Powell (1983, 1991) suggested that coercive pressure is a powerful constituency, which emanates from political and legal forces of the government and is likely to influence the way organizations operate in a particular context. In the Chinese context, various researchers (Ma and Lu, 2017;Yan et al, 2017;Zhang et al, 2014) argued that weak legal enforcements necessitate strong political ties to facilitate firms' success. Mimetic pressure is described as organizations that imitate the best practices of their competitors in the industry when the environment or conditions are uncertain (Zhu et al, 2013).…”
Section: Institutional Forces and Knowledge Managementmentioning
confidence: 99%
“…More importantly, as per literature, some of factors have considered influential contributory role in SME export performance, such as entrepreneurial orientation (Amin et al, 2016;Boso et al, 2016;Cadogan et al, 2016b;Felzensztein et al, 2015;; export market orientation (Cadogan et al, 2016b;Imran et al, 2017;Samson & Mahmood, 2015;Singh & Mahmood, 2013); business network (Ajayi, 2016;Imran et al, 2017;Serrano et al, 2016;Shneor et al, 2016;Yan et al, 2017) and total quality management (Abeykoon & de Alwis, 2016; M. Lages et al, 2009). Furthermore, entrepreneurial orientation (EO) is a managerial capability which firms embark on innovation, proactiveness and risk-taking initiatives to sustain the competitive advantage, which leads to higher export performance (Imran et al, 2017;İpek, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Export market orientation is recognized as a dynamic capability, and it entails complex and coordinated sets of skills and knowledge about exporting activities that are entrenched in the firm's internal routines (Zou, Fang and Zhao, 2003). Business network resources are valuable because they are purposefully invested for the expectation of future higher rents (Adler and Kwon, 2002), and further network resources are relatively rare because the successful acquisition of such resources depends on path-dependent processes and social complexities (Ajayi, 2016;Yan et al, 2017). Total quality management (TQM) promotes the alignment between a firm's process and employees, which in turn create a unique, rare and hard to substitute resource which enables the firm to produce the competitive advantage (Reed, Lemak and Mero, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Numerous studies have examined the contributing factors of SMEs' export performance such as entrepreneurial orientation (Amin, Thurasamy, Aldakhil, and Kaswuri, 2016;Boso, Oghazi, Cadogan and Story, 2016;Felzensztein, Ciravegna, Robson and Amorós, 2015;Imran et al, 2018a), business network (Ajayi, 2016;Imran et al, 2017c;Serrano, Acero and Fernandez-Olmos, 2016;Shneor et al, 2016;Yan, He and Cheng, 2017), total quality management (Abeykoon and de Alwis, 2016;Imran et al, 2018a;Imran, Hamid, and Aziz, 2018b;Lages, Silva, and Styles, 2009), and export market orientation (Cadogan et al, 2016;Imran et al, 2017c;Samson and Mahmood, 2015;Singh and Mahmood, 2013). Entrepreneurial orientation (EO) is a managerial capability that enables firms to embark on innovation, proactiveness, and risk-taking initiatives to sustain the firms' competitive advantage (Imran et al, 2017c; in employment and 35 percent in exports (Bijaoui, 2017).…”
Section: Introductionmentioning
confidence: 99%